Management of Employee Performance Data and Backend Development of the IHSAN POS Web Application for Professional Workers at PT Pos Indonesia - Jose Elio Parhusip; Nava Gia Ginasta (RISTEC : Research in Information Systems and Technology, 2025)
Abstract: This internship aims to: (1) develop an employee performance input system that is more accurate and efficient; (2) design an Entity Relationship Diagram (ERD) and database structure to support employee data processing; and (3) build a backend system with role-based authentication and authorization. The scope of the study includes managing individual performance data, which was previously handled manually and prone to input errors. The methods used involve collecting second-quarter performance data, designing the ERD, and developing the backend of the IHSAN POS web application using JavaScript and Express, integrated with PostgreSQL, DBeaver, and Prisma. The results of the development show that the constructed backend system improves the efficiency of the performance evaluation process, enhances data integration, and simplifies digital and structured validation and reporting. In conclusion, the development of this system contributes significantly to improving the efficiency, accuracy, and transparency of employee performance evaluations and supports strategic decision-making related to incentives and career development. Further improvements are recommended in terms of security and automation to make the system more adaptive to organizational needs and technological advancements. Keywords: Performance Management, Backend Development, Human Resource Information System, Objective Key Result (OKR), Database Design.